Integrasi Teknologi Digital dalam Sistem Akuntansi untuk Meningkatkan Efisiensi dan Akurasi Data - Madinatul Munawwarah; Masyhuri, Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze the integration of digital technology into accounting systems and its implications for improving the efficiency and accuracy of financial data. The method used is a conceptual qualitative approach based on a literature review, examining scientific journals, academic books, and relevant publications related to accounting digitization. The results of the analysis indicate that the integration of digital technologies such as cloud computing, artificial intelligence, and ERP systems can improve operational efficiency through the automation of real-time data recording, processing, and reporting. Digital technologies also contribute to enhancing data accuracy through automated validation mechanisms, data consolidation, and system-based error detection. The effectiveness of implementation is significantly influenced by infrastructure readiness, human resource competencies, and the organization’s ability to manage change. This study confirms that the relationship between digitization, efficiency, and accuracy is complex and non-linear. The integration of digital technologies must be understood as a continuous transformation process within modern accounting systems.